Short-term plyometric training improves running economy in highly trained middle and long distance runners - Saunders, P. U.; Telford, R. D.; Pyne, D. B.; Peltola, E. M.; Cunningham, R. B.; Gore, C. J.; Hawley, J. A. (The Journal of Strength and Conditioning Research, 2006)
Fifteen highly trained distance runners (O2max 71.1 +/- 6.0 ml/minkg, mean +/- SD) were randomly assigned to a plyometric training (PLY; n = 7) or control (CON; n = 8) group. In addition to their normal training, the PLY group undertook 3 x 30 minutes PLY sessions per week for 9 weeks. Running economy (RE) was assessed during 3 x 4 minute treadmill runs (14, 16, and 18 km/h), followed by an incremental test to measure VO2max. Muscle power characteristics were assessed on a portable, unidirectional ground reaction force plate. Compared with CON, PLY improved RE at 18 km/h (4.1%, p = 0.02), but not at 14 or 16 km/h. This was accompanied by trends for increased average power during a 5-jump plyometric test (15%, p = 0.11), a shorter time to reach maximal dynamic strength during a strength quality assessment test (14%, p = 0.09), and a lower VO2-speed slope (14%, p = 0.12) after 9 weeks of PLY. There were no significant differences in cardiorespiratory measures or VO2max as a result of PLY. In a group of highly-trained distance runners, 9 weeks of PLY improved RE, with likely mechanisms residing in the muscle, or alternatively by improving running mechanics.